The Diffusion of Human Resource Management Innovations - Beaumont, P. B. (Relations Industrielles / Industrial Relations, 1985)
This paper uses a sample of some 300 plants in Britain to examine the extent and nature of inter-organisational diffusion of human resource management innovations.